Political Equality in Allameh Sayyid Mohammad Hossein Tabatabaʾi’s Political Thought - ali maleki (Journal of Islamic Political Studies, 2022)
One of the important discussions in the political thought is the equality or inequality of human beings. Any image about equality can have a variety of effects in people’s political life. Investigating and explaining the view of Islamic thinkers on this subject can be useful, both theoretically and practically, in strategies of the states and Islamic societies. The main questions here are posed as follows: “What is the view presented by Allameh Tabatabaʾi as the Islamic philosopher and commentator of the Quran about the political equality?” and “Are the society members equal from the angel of the nature and from the theoretical viewpoint in political participation, administering the society and political power?” The hypothesis of this article is that the political equality has not been used directly as a topic in Allameh Tabatabaʾi’s works; but considering his system of thoughts and posing the social and political issues, we can extract his views on political thought. Accordingly, the principles of political equality such as the equal basic rights in relation to others and in the relationship between the state and the individuals and equality before law have been accepted. This study has used the descriptive-analytical method and content analysis to extract Allameh Tabatabaʾi’s views. In the light of citizen rights, people can – considering their equal role in social administration – choose the ruler and the form of ruling through consultation, and can have the right to policy-making and supervising in making legislation and decision-making related to administering the society. People enjoy equal right and equal votes in ruling and administering the society.